2015
DOI: 10.3389/fphys.2015.00293
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-dependent myoprotective effects of resveratrol on muscle injury induced by compression

Abstract: Our current understanding on the molecular mechanisms by which sustained compression induces skeletal muscle injury is very limited. This study aimed to test the hypothesis that activation of SIRT1 by the natural antioxidant resveratrol could deactivate apoptotic and catabolic signaling in skeletal muscle exposed to moderate compression. Two cycles of 6-h constant pressure at 100 mmHg was applied to the tibialis region of right, but not left hindlimbs of Sprague Dawley rats pre-treated with DMSO (vehicle contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In the present study experiments, treatment with resveratrol significantly activated the protein expression of SIRT1 in osteoporosis rats. Sin et al supported that resveratrol has an effect on muscle injury induced by compression through SIRT1 protein expression (31). Lee et al (14) also showed that resveratrol induces human keratinocyte damage through the activation of SIRT1 (14).…”
Section: Discussionmentioning
confidence: 76%
“…In the present study experiments, treatment with resveratrol significantly activated the protein expression of SIRT1 in osteoporosis rats. Sin et al supported that resveratrol has an effect on muscle injury induced by compression through SIRT1 protein expression (31). Lee et al (14) also showed that resveratrol induces human keratinocyte damage through the activation of SIRT1 (14).…”
Section: Discussionmentioning
confidence: 76%
“…Resveratrol, a natural antioxidant, mediates anti-apoptotic and anti-catabolic effects on compression injury in skeletal muscle by activation of SIRT1. [48]. Previous study showed that SIRT1 could improve muscle mass and functions by enhancing the regenerative capacity of muscles [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our present in vivo results demonstrated that SIRT1 exerted neuroprotective effect by inhibiting caspase-3 activity in rats with CIRI. Sin et al suggested that the effects of resveratrol on muscle injury were mediated through SIRT1, p53 and caspase-3 in skeletal muscle (26).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the decreased expression of SIRT1 may contribute to the increased expression of p53 protein in rats with CIRI. Sin et al suggested that the effects of resveratrol on muscle injury were mediated through SIRT1, p53 and caspase-3 in skeletal muscle (26). With neurotransmitter functions, NO is an important signaling and effector molecule, which extensively participates in physiological and pathological events (27).…”
Section: Discussionmentioning
confidence: 99%